Making Simple Biotechnology Products for Teachers at AL-Hidayah Waqf Foundation Hatyai Thailand as a Supplement to Teaching Materials - Indriyanti, Dyah Rini; Widiyatmoko, Arif; Fibriana, Fidia; Subali, Bambang; Darmawan, Melissa Salma (Journal of Community Empowerment, 2024)
Biotechnology is one of the concepts taught in science learning which is complex and dynamic and has a relationship between the application of science and technology. The application of biotechnology is very beneficial in various aspects of life. The importance of applying biotechnology in life encourages schools to provide learning platforms for students to learn about biotechnology processing properly. However there are still issues with biotechnology processing at partner schools. Specifically, they still don't know how to properly create basic biotechnology learning supplements or process biotechnology products. This inspired the UNNES Postgraduate School service team to assist with training in the creation of basic biotechnology goods at the Al-Hidayah Waqaf Foundation in Hatyai, Thailand, as an addition to instructional resources. This training aims to provide training in making simple biotechnology products so that they can improve educators' skills in packaging supplements for simple biotechnology teaching materials as well as identifying the benefits of apple and pineapple vinegar as well as training skills in making apple and pineapple vinegar correctly. The training method was implemented by providing tools and materials, presenting the material, and providing assistance in the practice of making apple and pineapple vinegar biotechnology. The training has been carried out well. The results of the training can help teachers prepare science learning that is contextual and has an entrepreneurial spirit.